COPD as a risk factor for Coronary Artery Disease (CAD): Overview of 10-year atherosclerotic cardiovascular disease (ASCVD) risk assessment - Buklioska Ilievska, Daniela; Mickovski Ivana; Baloski Marjan; Doneva Daniela; Neshovska Radmila; Simeonova Magdalena; Nedeska Minova Natasha; Prgova, Biljana; Minov, Jordan; Kochovska Kamchevska Nade; Bushev Jane; Trajkovska Vanche (My University, 2022)
We aimed to investigate the association between COPD and CAD (overview of 10-year risk of fatal cardiovascularevent), and the relation to the severity of airflow limitation.Cross-sectional study including 220 patients with stable COPD as investigated group (IG), aged 40 to 75 yearsand 58 non-COPD subjects, matched by gender, age, BMI, smoking status, as control group (CG). All studysubjects underwent pulmonary, cardiological evaluation, lipid and glycemic status.The analysis compared the 10-year established ASCVD risk between COPD stages (according to GOLDclassification 1, 2, 3, 4) and between IG vs. CG. ASCVD score was classified as low (score <5%), borderline (5 to<7.5%), moderate (≥7.5 to <20) and high risk (score ≥20%). Results presented statistically significant differencebetween mean ASCVD value in IG 21,69±13,86% vs. CG 15,83±9,92% (p=0.0028). The median risk of ASCVDfor fatal cardiovascular events was high in IG and moderate in CG. The mean and median values of 10-yearASCVD risk in the IG subgroups were: GOLD1 16,79±8,04% (50% of the subjects with risk >15,7%), GOLD222,67±16,49% (50% of the subjects with risk >20,6%), GOLD3 26,81±14,15% (50% of the subjects with risk >27,6%) and GOLD4 20,70±13,52% (50% of the subjects with risk > 18,4%). The average ASCVD risk of fatalcardiovascular event was moderate in GOLD1 and GOLD4, and high in GOLD2 and GOLD3.We found higher risk for fatal cardiovascular outcome in patients with COPD, even in the early COPD stages(GOLD2), compared to non-COPD group. Our findings suggest that an urgent need to develop comprehensivestrategies for prevention, screening and early treatment are needed.
Keywords: COPD; COPD - management; chronic diseases